The anti-caries effects of dental adhesive resin influenced by the position of functional groups in quaternary ammonium monomers. Issue 3 (March 2018) - Liang, Jingou; Li, Mingyun; Ren, Biao; Wu, Tianmu; Xu, Hockin H.K.; Liu, Yong; Peng, Xian; Yang, Ge; Weir, Michael D.; Zhang, Shiyong; Cheng, Lei; Zhou, Xuedong
Graphical abstract: Highlights: Quaternary ammonium monomers (QAMs) with different position of the functional groups were synthesized and added into adhesives. The effect of the changed position of the functional groups on the mechanical properties, anti-biofilm activity and biocompatibility of the modified adhesive were investigated. The anti-bacterial mechanism of adhesive system modified by QAM was further investigated. Abstract: Objectives: A new quaternary ammonium monomer (QAM), triethylaminododecyl acrylate (TEADDA) was synthesized, in which the position of the functional groups was different from that of dimethylaminododecyl methacrylate (DMADDM). The objectives were to: (1) investigate the effect of the changed position of the functional groups on the mechanical properties, anti-biofilm activity and biocompatibility of adhesive resin, and (2) study the anti-bacterial mechanism of QAM to improve the performance of the adhesive system modified by QAM. Methods: TEADDA and DMADDM were added into adhesives. Microtensile bond strength and surface charge density were measured. Multi-species biofilms were incubated on specimens for 16 h, 48 h and 72 h and analyzed via MTT assay, lactic acid measurement and confocal laser scanning microscopy. The ratio of different species of bacteria was measured by real-time polymerase chain reaction. Cytotoxicity and biocompatibility were analyzed by eluents cytotoxicity test and histological images of H&E staining via an animal study in rats. Results: The mass fraction of TEDDA allowed to be added into adhesive was higher than that of DMADDM. However, even 10% TEADDA did not yield a strong anti-biofilm effect on biofilm growth, lactic acid production and bacteria compositions. TEADDA added into adhesives showed better mechanical properties but weaker anti-bacterial effect. There was no significant difference on cytotoxicity and biocompatibility between DMADDM and TEADDA. Significance: The study could be helpful for the investigation of the anti-caries mechanism of QAMs, the design of new QAMs and the improvement of the anti-caries activity of the modified dental materials.